ANALISIS TINGKAT KEPUASAN KONSUMEN DENGAN METODE NET PROMOTER SCORE (NPS) DAN CUSTOMER EFFORT SCORE (CES) PADA PENGGUNA KARTU TELKOMSEL DI SAMARINDA - Darlan; Mardiono; Syarifah Lulu Zannati; Muhammad Fadli (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
Analysis of Consumer Satisfaction Levels Using the Net Promoter Score (NPS) and Customer Effort Score (CES) Methods on Telkomsel Card Users in Samarinda. The purpose of the study was to measure the level of consumer satisfaction and ease of service for Telkomsel card service users in Samarinda. This research method is quantitative descriptive, which is a research method that uses quantitative data to describe the characteristics of a phenomenon or population, without testing the relationship or determining the cause and effect between variables. The population is all consumers who use Telkomsel card services in Indonesia, totaling 8510 users (as of September 2023). The sample size collected was 158 respondents (minimum sample of 99 based on the Slovin formula). The type of data is primary data or internal data obtained directly from respondents. The data collection technique uses a questionnaire. The data analysis technique uses the Net Promoters Score (NPS) method, which is a method for measuring consumer satisfaction, and the Customer Effort Score (CES) method, which is a method for measuring the ease of consumer experience with product/company services. The assessment scale for each respondent's answer is scored from 0-10, where 0 means very unlikely/very difficult, and 10 means very possible/very easy. The survey results from 158 respondents who were collected showed that Telkomsel had a CES index on a scale of 7-10 (very easy), namely 7.47 in the